Direct-Fed microbials for receiving cattle I: Effects of ProTernative stress formula fed in a liquid suspension on growth and health performance of receiving beef heifers - A.V. Siverson; M.E. Corrigan; James J. Higgins; Dale A. Blasi; Brandon E. Oleen (Kansas Agricultural Experiment Station Research Reports, 2012)
Lightweight stocker calves experience variable degrees of physiological stress resulting from weaning, transport, food and water deprivation, diet changes, inclement weather, and infectious diseases. Consequently, preconditioning and specialized nutrition that include direct-fed microbials may become more common in the beef industry as a means of controlling disease and minimizing the effects of stress.
Keywords: Cattlemen& #x27; s Day; 2012; Kansas Agricultural Experiment Station contribution; no. 12-231-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1065; Beef Cattle Research; 2012 is known as Cattlemen& #x27; s Day; Beef; ProTernative stress formula; Growth performance; Health performance; Microbials